Framework for Managing Multicultural Based Islamic Education in Schools - Salim, Nur Agus; Mustainah, Mustainah; Cakranegara, Pandu Adi; Susanto, Moh.Rusnoto; Suasa, Suasa (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2023)
This study aims to analyze the management framework of multicultural-based Islamic religious education in elementary schools. This study uses a qualitative approach with a phenomenological approach. The locus of this research is SDN 1 Kota Bangun. To obtain data, the authors conducted interviews, observations, and documentation. Data reduction procedures, data presentation, and concluding analyzed the collected data. The study results show that the management of multicultural-based Islamic Religious Education learning must be carried out by planning, implementing and evaluating learning that is carried out in totality, integrated, involving all parties and is sustainable to provide optimal results. This research has implications for the importance of religious moderation education from an early age to anticipate students' exclusive and intolerant attitudes.